The dynamic expression of SOX17 in germ cells from human female foetus and adult ovaries after specification - Luo, Ying-Yi; Jie, Hui-Ying; Huang, Ke-Jun; Cai, Bing; Zhou, Xiu; Liang, Ming-Yi; Zhou, Can-Quan; Mai, Qing-Yun (Frontiers in Endocrinology, 2023)
Background SOX17 has been identified as a critical factor in specification of human primordial germ cells, but whether SOX17 regulates development of germ cells after sex differentiation is poorly understood. Methods We collected specimens of gonadal ridge from an embryo (n=1), and ovaries of foetuses (n=23) and adults (n=3). Germ cells were labelled with SOX17, VASA (classic germ cells marker), phosphohistone H3 (PHH3, mitosis marker) and synaptonemal complex protein 3 (SCP3, meiosis marker). Results SOX17 was detected in both cytoplasm and nucleus of oogonia and oocytes of primordial and primary follicles from 15 to 28 gestational weeks (GW). However, it was exclusively expressed in cytoplasm of oogonia at 7 GW, and in nucleus of oocytes in secondary follicles. Co-expression rates of SOX17 in VASA+ germ cells ranged from 81.29% to 97.81% in foetuses. Co-staining rates of SOX17 and PHH3 or SCP3 were 0%-34% and 0%-57%, respectively. Interestingly, we distinguished a subpopulation of SOX17+VASA- germ cells in fetal ovaries. These cells clustered in the cortex and could be co-stained with the mitosis marker PHH3 but not the meiosis marker SCP3. Conclusions The dynamic expression of SOX17 was detected in human female germ cells. We discovered a population of SOX17+ VASA- germ cells clustering at the cortex of ovaries. We could not find a relationship between mitosis or meiosis and SOX17 or VASA staining in germ cells. Our findings provide insight into the potential role of SOX17 involving germ cells maturation after specification, although the mechanism is unclear and needs further investigation.